Pengaruh Peer Instruction Flipped Classroom dan Literasi Digital Terhadap Hasil Belajar Ekonomi Kelas XI BDP di SMKN 1 Surakarta - Slamet Effendy Yusuf; Sudarno Sudarno; Khresna Bayu Sangka (Jurnal Pendidikan Ekonomi (JUPE), 2022)
This research was carried out based on the phenomenon of online learning during the Covid-19 pandemic whose learning outcomes were below the KKM (Minimal Completeness Criteria). This condition is caused by the less innovative learning model and the lack of digital literacy in Eleven-grade students of Online Business and Marketing at SMK Negeri 1 Surakarta. The purpose of this study was to determine the effect of peer instruction flipped classroom and digital literacy on economic learning outcomes in online business materials. This research was in the form of a quasi-experimental research model with pretest and posttest group design. The analysis of the research data used the Independent Sample T-Test and N-Gain Test. The results showed that there were significant effects between peer instruction flipped classroom and digital literacy on cognitive learning outcomes. In collecting various research data, researchers used pre-test, post-test, and questionnaires. The results were processed using SPSS (Statistical Package for the Social Sciences) and were described in descriptive statistical analysis. The results of this study can be used as a solution in conducting a learning process that uses peer instruction flipped classrooms and digital literacy in a balanced way to create effective learning.